Measurement of the weak axial-vector coupling constant in the decay of free neutrons using a pulsed cold neutron beam - Märkisch, Bastian; Mest, Holger; Abele, Hartmut; Dubbers, Dirk; Roick, Christoph; Werder, Dominik (Physical review letters, 2019)
We present a precision measurement of the axial-vector coupling constant gA in the decay of polarized free neutrons. For the first time, a pulsed cold neutron beam was used for this purpose. By this method, leading sources of systematic uncertainty are suppressed. From the electron spectra we obtain λ=gA/gV=−1.27641(45)stat(33)sys, which confirms recent measurements with improved precision. This corresponds to a value of the parity violating beta asymmetry parameter of A0=−0.11985(17)stat(12)sys. We discuss implications on the Cabibbo-Kobayashi-Maskawa matrix element Vud and derive a limit on left-handed tensor interaction.
Gesehen am 07.08.2019